Comparison on the effectiveness of low pressure reverse osmosis membrane for the rejection of organic (Endocrine disrupting chemical: pentachlorophenol) with inorganic (Heavy metals :copper and iron) substances - 291528 Chung, Joan Dolly Zie Wei (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006